The information practices of law enforcement: Passive and active collaboration and its implication for sanctuary laws in Washington state. (12th May 2021) - Tian, Yubing; Gomez, Ricardo; Cifor, Marika; Wilson, James; Morgan, Henry
Abstract: Although Washington state sanctuary policies of 2017 prohibit collaboration between local law enforcement and federal immigration enforcement in noncriminal cases, compliance with sanctuary policies has not been systematically studied. We explore information practices and collaboration between local law enforcement and federal immigration enforcement in Grant County, Washington, based on records from November 2017 to May 2019 obtained by the University of Washington Center for Human Rights through Public Records Act (PRA) requests. Qualitative analysis of over 8, 000 pages reveals a baseline of passive and active information sharing and collaboration between local law enforcement and federal immigration agencies before Washington sanctuary laws went into effect in May 2019, a practice that needs to stop if agencies are to comply with the laws. We employ a systematic methodology to obtain (through PRA and other Access to Information requests) and analyze official records through qualitative content analysis, to monitor and hold local law enforcement accountable in their compliance with sanctuary laws. This method can be used to examine law enforcement information behaviors in other counties in Washington, and in other states that offer sanctuary protections, as a way to monitor compliance with sanctuary laws and strengthen the protection of immigrants' rights.